Myrica rubra Preharvest Treatment with Melatonin Improves Antioxidant and Phenylpropanoid Pathways During Postharvest Storage - Jun-Quan Chen; Yun-Shuang Ma; Hejiang Zhou; Rui-Xue Yu; Miao Xiong; Na Yang; Ji-Qiu Wang; Yang Tian; Ling-Yan Su (Foods)
Myrica rubra is known for its popularity and robust nutritional value. While fresh Myrica rubra fruit is a perishable commodity, it has a short post-harvest life and is susceptible to fungal decay after harvest. Melatonin has been reported to delay the aging and quality decline of various fruits and vegetables after harvest. However, the effects of pre-harvest melatonin treatment on the maintenance of post-harvest quality and storage extension of fresh Myrica rubra fruit are still unclear. The impact of pre-harvest spraying of melatonin at different concentrations (100 μM, 300 μM, and 500 μM) on the fruit quality of Myrica rubra during storage at room temperature or 4 °C was investigated. The results indicated that in the final stage of storage, compared with the control group, different concentrations of melatonin reduced the decay index by 13.0–47.1% and also decreased the weight loss, the content of O2−•, and the content of malondialdehyde (MDA), respectively. Meanwhile, melatonin increased the content of antioxidants such as superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), as well as the total polyphenols and flavonoids content. Finally, RNA transcriptome sequencing revealed that melatonin enhanced the antioxidant capacity by increasing the expression of both antioxidant enzymes and changing phenylpropanoid pathway-related genes, therefore maintaining the fresh Myrica rubra quality. Our findings uncovered a potent role and mechanism of melatonin in maintaining Myrica rubra fruit quality during storage and suggest that pre-harvest melatonin spraying may be a convenient and effective method for prolonging storage and maintaining quality of fruits after picking.